2018
DOI: 10.5586/asbp.3576
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forest cover in Sudety Mountains during the last 250 years: patterns, drivers, and landscape-scale implications for nature conservation

Abstract: Historical ecology gives a reference point to explain the contemporary state of particular ecosystems as well as entire landscapes. In this study, we examined the quantitative changes in forest cover in the central part of the Sudety Massif (area ca. 1,120 km 2 ) during the last 250 years. The information regarding forest patch distribution and its changes was derived by comparison of maps from 1747 and the 1970s drawn at scales of 1:33,000 and 1:25,000, respectively. To examine the effect of environmental var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Land cover analyses showed that the area covered by forests within the present limits ofŚlęża Landscape Park increased from 29.32% at the end of the 19th century to 33.80% in 2013. Szymura et al indicate that forest area increased of the entire Sudeten area from 30.4% in the 18th century to 36.4% in the 20th century [56]. The same situation has also been observed in other mountainous areas in Poland.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Land cover analyses showed that the area covered by forests within the present limits ofŚlęża Landscape Park increased from 29.32% at the end of the 19th century to 33.80% in 2013. Szymura et al indicate that forest area increased of the entire Sudeten area from 30.4% in the 18th century to 36.4% in the 20th century [56]. The same situation has also been observed in other mountainous areas in Poland.…”
Section: Discussionmentioning
confidence: 71%
“…The slopes ofŚlęża and surrounding hills have been covered with forests for years, and settlement areas are developing in the foothills, while arable land dominate in flat areas. Weak soil is mentioned in literature as the basic driving force behind changes in forest landscapes [63]; however, as shown by Szymura et al [56], in the Sudety area, the soil type has not had a significant impact on landscape changes. Analyses of the driving forces of changes in forest landscapes have mainly concerned the Carpathian area [19,60,64], with its Polish part investigated less frequently [60,65].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Within the research area no natural phenomena were observed in the analyzed period that could direct affect landscape changes, except for small local floods caused by heavy rains in 1964, 1997 and 2013. Type of soil did not affect the changes in forest landscapes in the whole Sudety and Przedgorze Sudeckie area [52] that's why we did not take this factor into account. Therefore, due to the kind of the research area, we assumed that among natural driving forces, the topography could be one of those that most influenced the forest landscape changes in analyzed period of time.…”
Section: Natural Driving Forces Of Landscape Changementioning
confidence: 94%
“…On the other hand, growth managed forests in Central Europe occupy a significant area and certain parts of them are both economically and environmentally valuable. Despite the ecological research mainly focusing on the remnants of primeval forests or forest habitats with lower human impact [29][30][31], some local studies also deal with various aspects of managed temperate forests ecology [32][33][34]. As indicated in some studies [35,36], there are ESGs of herbaceous species in lowland coppice forests.…”
Section: Introductionmentioning
confidence: 99%